O pós-guerra encenado por R.W. Fassbinder: instabilidade e equilíbrio na composição das formas cinematográficas - Roberto Ribeiro Miranda Cotta (2016)
This thesis analyzes the stylistic joints designed by the films The marriage of Maria Braun (1978), Lola (1981) and Veronika Voss (1982), which form the Postwar Trilogy by Rainer Werner Fassbinder. Acclimated between the 1940s and 1950s in German territory distributed by Occupation Zones or in Adenauers Germany, these films add aesthetic, narratives and dramaturgical forms scanned on the threshold between harmony and spin, the arrangement and disorder, the hierarchy and entropy, the organization and breakpoints. In this sense, the main objective of this study is to investigate how the coexistence and friction between structural polarities so different are rooted in formalistic bases of these movies, acting intrinsically in building a particular cinematographic style. Thus, the theoretical framework is driven by concepts the history of cinema and modern cinema, while the methodology follows a qualitative approach crossed by visual, sound, dramatic and logical narrative criteria of film analysis.